ANALISIS PENGARUH KONTRIBUSI PAJAK KENDARAAN BERMOTOR DAN BEA BALIK NAMA KENDARAAN BERMOTOR TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI PROVINSI KALIMANTAN SELATAN TAHUN 2003-2012 - Ruslinda Agustina; Rina Arliani (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2015)
Abstract, This research aimed to examine the effect of the contribution of the PKB and BBNKB to PAD in South Kalimantan province in 2003-2012. The method used quantitative methods, namely measurement of objective statistical data and through SPPS version 16. The results of the test or test the hypothesis partially explains PKB t affect the PAD, while BBNKB no effect on the South Kalimantan provincial PAD period 2003-2012. The results of hypothesis testing simultaneously or PKB and BBNKB F test against provincial PAD bepengaruh South Kalimantan period 2003-2012. the results of the regression estimates indicate that there are two independent variables in the regression model is able to explain 64% of the revenue and the balance of 36% is explained by other variables not included in this study.